Fabrication and unraveling the morphological, structural, and dielectric features of PMMA-PEO-SiC–BaTiO3 promising quaternary nanocomposites for multifunctional nanoelectronics applications - Jaafar, Hiba Kamil; Hashim, Ahmed; Rabee, Bahaa H. (Journal of materials science. Materials in electronics, 2024)
The current work aims to fabricate of barium titanate (BaTiO 3 ) and silicon carbide (SiC) nanostructures doped blended of poly-methyl methacrylate (PMMA) and polyethylene oxide (PEO) to apply in promising pressure sensors and electronics applications. The morphological, structural, and dielectric properties of (PMMA-PEO/BaTiO 3 –SiC) nanocomposites were investigated. The Fourier transform infrared spectroscopy (FTIR), optical microscopic(OM) and scanning electron microscope(SEM) measurements were examined. The dielectric properties were studied at frequency ranged from 100 Hz to 5 × 10 6 Hz. The results of dielectric properties confirmed that the dielectric constant ( ε ′) and dielectric loss (ε′′) of (PMMA-PEO/BaTiO 3 –SiC) nanocomposites decreased with increasing frequency, while they tend to increase when the ratio of (BaTiO 3 –SiC) NPs increased. The A.C conductivity of (PMMA-PEO/BaTiO 3 –SiC) nanocomposites enhanced with rising frequency and ratio of (BaTiO 3 –SiC) NPs. The (PMMA-PEO/BaTiO 3 –SiC) nanocomposites examined for the pressure sensors application in the pressure range of 80–160 bar. The findings indicated to enhance of dielectric factors with rising pressure. Finally, findings of morphological, structural and dielectric properties confirmed that the (PMMA-PEO/BaTiO 3 –SiC) nanocomposites have individual characteristics compared of other nanomaterials which make it significant technologically in the development of several advanced microelectronic and promising optoelectronic devices.